EFEKTIVITAS PENAMBAHAN EKSTRAK UBI JALAR UNGU (Ipomoea batatas var. Ayamurasaki) DAN SUSU SKIM TERHADAP KADAR ASAM LAKTAT DAN pH YOGHURT JAGUNG MANIS (Zea mays L. Saccharata) DENGAN MENGGUNAKAN INOKULUM Lactobacillus acidophilus DAN Bifidobacterium sp. - Irda Sayuti; Sri Wulandari; Dian Kurnia Sari (Biogenesis, 2013)
This research aims to know the effectiveness addition of purple sweet potatoes extract and skim milk to sweet corn yoghurt’s lactic acid and pH by using Lactobacillus acidophilus and Bifidobacterium sp. The research held in Biological Laboratory of Educational Faculty and Chemical Laboratory Of Result and Fishery of Riau University. Research design has been used was factorial completed randomized design (RAL factorial) which consisted of two factor. First factor is the addition of purple sweet potatoes extract with concentration are 0%, 5%, 10%, 15% and second factor is skim milk with concentration are 0%, 3%, 5%, 7%. Parameter of research consisted of lactic acid and pH which analysed by using the ANAVA and continued with DMRT level 5%. The result showed that the addition of purple sweet potatoes extract and skim milk affected sweet corn yoghurt’s lactic acid and pH significantly. The combination of purple sweet potatoes extract and skim milk addition most effective at U15S5 (purple sweet potatoes extract 15%, skim milk 5%) with lactic acid 1.216% and pH 3,623.Keywords : Yoghurt, Lactic Acid, pH.